CONNECTED SPEECH PROCESSES IN DIFFERENT STYLES OF ENGLISH - Fayzulloyeva Zilola Zafarovna; Ramozonova Dilnura (TADQIQOTLAR, 2026)
Annotation This article will provide information about connected speech that differs between formal and informal styles. Casual, spontaneous conversations often show numerous reductions and elisions, whereas formal or prepared speech maintains clearer articulation and controlled rhythm. Research by Gillian Brown and Rodney Huddleston demonstrates that such phonetic differences are socially meaningful, signaling formality, emphasis, emotion, and interpersonal interaction. In addition, connected speech contributes to expressing social identity, regional affiliation, and group membership.